(untitled) (Swiss Medical Weekly, 2020)
Systemic sclerosis is a rare autoimmune disease characterised by a multifactorial aetiology involving a gene–environment interaction. Despite the growing epidemiological arguments for odds ratio (OR) data showing an association with occupational exposure, systemic sclerosis is not currently included in the list of recognised occupational diseases in Switzerland, unlike other northern European countries. Future recognition will be conditional on the demonstration of a strong association between the disease and occupational exposure in the scientific literature. The present article’s main goal is to present five cases of systemic sclerosis investigated for possible occupational aetiologies during occupational pathology consultations at the Institute for Work and Health, in Lausanne. The occupational aetiologies of these cases are discussed against the background of a literature review of publications from the past 20 years in order to determine whether recognition as an occupational disease is possible within Switzerland’s legal framework. Epidemiological studies of systemic sclerosis have identified strong associations with occupational factors such as exposure to silica and solvents, with ORs >2, and weaker associations with epoxy resins and welding fumes. Other occupational exposures are also known to induce systemic sclerosis-like diseases, such as vinyl chloride disease and toxic oil syndrome. All five patients had been exposed to either silica, solvents, or both. Given their exposure and the data in the literature, four patients had their cases declared to their accident insurance companies and two of them were recognised as suffering from an occupational disease by the Swiss National Accident Insurance Fund. Our literature review enabled us to design a short questionnaire to help general practitioners and rheumatologists to identify those patients with systemic sclerosis who are likely to have their illness recognised as an occupational disease.